MicroRNA-215 impairs adipocyte differentiation and co-represses FNDC3B and CTNNBIP1. (October 2016) - Peng, Yongdong; Li, Huanan; Li, Xianglong; Yu, Shulong; Xiang, Hong; Peng, Jian; Jiang, Siwen
Abstract: MicroRNAs (miRNAs) are small ∼22 nucleotide regulatory RNAs that regulate the stability and translation of cognate mRNAs. MiRNAs participate in the regulation of adipogenesis, and identification of the full repertoire of miRNAs expressed in adipose tisse is likely to improve our understanding of adipose tissue growth and development significantly. In the present study, miR-215-5p was found to inhibit adipocyte differentiation of 3T3-L1 cells. Moreover, fibronectin type III domain containing 3B ( FNDC3B ) and catenin, beta interacting protein 1 ( CTNNBIP1 ) were found to be direct targets of miR-215-5p. Further studies in mouse 3T3-L1 cell-line suggests that miR-215-5p is a negative regulator of adipocyte differentiation through post-transcriptional regulation of FNDC3B and CTNNBIP1 during early adipogenesis.